Contemporary flâneuses in late capitalism: the representation of urban space in two Hong Kong women artists' works - Zeng, Hong (Continuum (Mount Lawley, W.A.), 2020)
In literature on modern urban life, a flâneur is a man who wanders seemingly aimlessly but with the intention of observing people or events in urban life and perhaps recording these observations in text or images. This article shows how contemporary women artists in Hong Kong-a city in late capitalism, perform the role of the flâneuse, the female counterpart of the flâneur. The article analyses Stella Tang's series of paintings Sauntering Through My City Series (2009-2016) and Annie Wan's ceramic works Looking For Poetry in Wanchai (2005) and Collecting Moonlight (2017). The article takes a nomadic nondialectical approach to explore how the two women artists practise their flâneurie, and how they transform such experiences into art projects that are different from the conventional flâneur art. I identify three aspects of the alternative representation of urban space in the works of the two flâneuses: reconfiguration of conception, the creative appropriation of alternative art forms and public engagement.